2-Chloro-N?-[4-(dimethylamino)benzylidene]-N-[4-(3-methyl-3-phenylcyclobutyl)-1,3-thiazol-2-yl]acetohydrazide - Inkaya, Ersin; Dincer, Muharrem; Cukurovali, Alaaddin; Yilmaz, Engin (Int Union Crystallography, 2011)
The molecular conformation of the title compound, C25H27ClN4OS, is stabilized by an intramolecular benzylidine C-H center dot center dot center dot N-thiazole hydrogen bond. The thiazole ring makes dihedral angles of 12.0 (3) and 20.4 (2)degrees, respectively, with the phenyl and benzene rings, while the phenyl and benzene rings make a dihedral angle of 22.6 (2)degrees. The crystal packing involves weak intermolecular thiazole C-H center dot center dot center dot O-carbonyl and methyl C-H center dot center dot center dot pi hydrogen-bonding associations.
Keywords: Schiff-Bases; Tautomerism